2008
DOI: 10.1007/s00404-008-0780-7
|View full text |Cite
|
Sign up to set email alerts
|

Fetal macrosomia in African women: a study of 249 cases

Abstract: The higher the total body weight at birth, the higher the rate of macrosomia. Macrosomia had implications for high morbidity and mortality in the mothers and their infants. Delivery methods need to be evaluated. Caesarean section should be more readily used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
62
5
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(94 citation statements)
references
References 4 publications
15
62
5
7
Order By: Relevance
“…8-22.8). This is in accordance with the findings of Kamanu et al [14] who noticed that past history of delivery of a macrosomic baby was a significant risk factor for the delivery of macrosomic baby in subsequent pregnancies.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…8-22.8). This is in accordance with the findings of Kamanu et al [14] who noticed that past history of delivery of a macrosomic baby was a significant risk factor for the delivery of macrosomic baby in subsequent pregnancies.…”
Section: Discussionsupporting
confidence: 94%
“…Regarding pre-gestational BMI, we observed that women with BMI C25 had slightly increased risk for This is in accordance with the findings of Bergmann et al [13] who noticed that women with pre-gestational BMI C26 kg/m 2 were at increased risk for delivering macrosomic babies, while Kamanu et al [14] found a pre-gestational BMI value of C28 kg/m 2 as cut-off point for the risk for delivering macrosomic babies. Moreover, father's BMI C30 was found in our study to have an influence in the occurrence of macrosomia (OR 3.7, 95 % CI 1.7-6.9).…”
Section: Discussionsupporting
confidence: 93%
“…Por otra parte, no pudimos determinar si la cesárea fue electiva o de emergencia. En cualquier caso, debido a que la macrosomía se asoció con la obesidad materna, como se ha reportado previamente (19,20) , la reducción de la obesidad puede reducir la macrosomía, disminuyendo así las complicaciones en el parto y el puerperio y las tasas de cesáreas. Además, la reducción de la macrosomía puede contribuir a prevenir el desarrollo de sobrepeso / obesidad en la infancia (21) .…”
Section: Discussionunclassified
“…Fetal and neonatal macrosomia induced by maternal diabetes have long been recognized in human pregnancy (Gilmartin et al 2008, Kamanu et al 2009). Macrosomia was also observed in case of increased maternal fat intake (Soulimane-Mokhtari et al 2005, Coe 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Fetal macrosomia often demands the attention of different medical disciplines. It has been previously defined in human as a birth weight above 4000 to 4500 g. It may be associated with a higher risk of birth injury during vaginal delivery (Kamanu et al 2009, Iessi et al 2010, Al-Wazzan and Sarsam 2011. Macrosomia has different causes.…”
mentioning
confidence: 99%